A correlational study on the experiences of family members of trans and gender diverse people in Portugal - Gonçalves, B.; António, R.; Moleiro, C. (International Journal of Transgender Health, 2025)
Introduction: Research on the experiences of family members of transgender and gender diverse (TGD) people remains limited, despite their crucial impact on the well-being of TGD individuals. This study aimed to fill this gap, by investigating their experiences within the wider ecological context that influences them. Method: A sample of 87 parents, siblings, partners, children, and extended family members of TGD people (Mage = 39.9) were surveyed through questionnaires about their reactions and concerns regarding the disclosure of their TGD relatives, experiences in education and health contexts, and perceptions of the Portuguese legal framework. Results: The results revealed largely positive reactions to disclosure, favorable experiences with healthcare services, and optimistic views of the Portuguese legal framework. Average scores were reported regarding distress and concerns at the time of disclosure and experiences with the education system. Additionally, results revealed a significant correlation between greater concerns and more negative reactions to disclosure. Discussion: These findings highlight the need for support and resources for family members of TGD people and wider dissemination of information on gender identity issues.